Peningkatan Produktivitas dan Pemasaran Digital UMKM Getah Gambir di Desa Salak II Kabupaten Pakpak Bharat - Silaban, Saronom; Ulgari, Siti; Siahaan, Sabda Dian Nurani; Ruslan, Dede; Boangmanalu, Eka Putra Dairi; Lukman, Mena Fadilia; Sibarani, Choms Gary Ganda Tua (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aims to optimize gambier production through the application of an Appropriate Technology (TTG) pressing machine, facilitate the design of modern packaging, and strengthen digital marketing strategies and basic financial management for the “Merandal Majuna” business group in Salak II Village, Pakpak Bharat Regency. The method employed was a participatory approach through integrated intervention. The evaluation instruments included observation sheets, interviews, and documentation, which were analyzed using comparative descriptive techniques. The results of this program show a significant increase in productivity, as the Appropriate Technology (TTG) machine was able to process more than 30 kg of gambier leaves per cycle, far exceeding manual methods. In addition, the market reach expanded from the local level to wider markets through the use of digital platforms such as Instagram, Shopee, and Facebook Marketplace. The partners also developed basic skills in systematic financial record-keeping.